COVID 19-Fighting an unseen enemy - Vasantha Kamath; Shreyashi Ganguly; B Nivea (Wolters Kluwer Medknow Publications, 2020)
In December 2019, a previously unknown coronavirus, named SARS-CoV-2, was discovered in Wuhan, Hubei province of China. It was sequenced and isolated by January 2020. SARS-CoV-2 is associated with an ongoing outbreak of atypical pneumonia (Covid-2019) that has affected over 2,118,700 people and killed more than 141,900 of those affected in >210 countries as of April 16, 2020. Community-acquired coronaviruses are ubiquitous. COVID-19 is predominantly seen in older population with chronic medical conditions. There is a male preponderance. Median age was 55-59 years. SARS-CoV-2 is also more likely to infect people with chronic comorbidities such as cardiovascular and cerebrovascular diseases and diabetes. Coronavirus has an R0 of 3.28. Unlike European countries and USA, majority of the cases in India were affecting people of age group between 31 and 40 years. Mortality rate is around 3.34%. WHO, described three main transmission routes for the COVID-19: 1) droplets transmission, 2) contact transmission, and 3) aerosol transmission. COVID presents with fever, dry cough, dyspnoea, chest pain, fatigue and myalgia. Less common symptoms include headache, dizziness, abdominal pain, diarrhoea, nausea, and vomiting. Characteristic cutaneous, haematological, gastrointestinal, neurological manifestations are also seen. Testing with RT-PCR, antibody testing, and quarantine, social distancing, contact tracing are the only arsenals to reduce the burden. Every case is different; beyond standard antipyretics, anti-tussives, the role of ventilation, anticoagulation, antivirals, steroids, hydroxychloroquine, retroviral agents are still being dynamically assessed. In the absence of dedicated cures, vaccines, the novel coronavirus, is a challenge and exercise of public health measures and effective governance like no other phenomenon in the 21st century.